Nanotechnology in medicine and relevance to dermatology: Present concepts - K H Basavaraj (Wolters Kluwer Medknow Publications, 2012)
Nanotechnology and nanomedicine are complementary disciplines aimed at the betterment of human life. Nanotechnology is an emerging branch of science for designing tools and devices of size 1-100 nm, with unique functions at the cellular, atomic and molecular levels. The concept of using nanotechnology in medical research and clinical practice is known as nanomedicine. Today, nanotechnology and nanoscience approaches to particle design and formulations are beginning to expand the market for many drugs and forming the basis for a highly profitable niche within the industry, but some predicted benefits are hyped. Under many conditions, dermal penetration of nanoparticles may be limited for consumer products such as sunscreens, although additional studies are needed on potential photooxidation products, experimental methods and the effect of skin condition on penetration. Today, zinc oxide and titanium dioxide nanoparticles (20-30 nm) are widely used in several topical skin care products such as sunscreens. Thus, in the present scenario, nanotechnology is spreading its wings to address the key problems in the field of medicine. The benefits of nanoparticles have been shown in several scientific fields, but very little is known about their potential to penetrate the skin. Hence, this review discusses in detail the applications of nanotechnology in medicine with more emphasis on the dermatologic aspects.